Digest: Will invaders adapt to climate change?. (26th November 2019) - Schumm, Matthew P.
Abstract: One hypothesis for invasive species' success is that they show high potential to evolve in response to environmental change. Logan et al. evaluate this hypothesis in the invasive harlequin ladybeetle ( Harmonia axyridis ), using a breeding experiment to determine the genetic architecture of traits underlying thermal tolerance. Lack of heritable variation in some of these traits, and genetic correlations leading to trade‐offs in others, suggest this species has limited potential to evolve in response to climate change.